Trauma, media, art : new perspectives - Broderick, Mick; Traverso, Antonio (Cambridge Scholars, 2010)
During the past one hundred years or so, the depiction of traumatic historical events and experiences has been a recurrent theme in the work of artists and media professionals-including those in literature, theatre, visual art, architecture, cinema, and t.